Criptodática: criptografia como uma proposta didática para o estudo de funções afins e suas inversas - RODRIGUES, Luciana dos Santos (Instituto Federal do Amapá, 2021)
The present work involves a proposal of associating the Cryptography theme to the Content of Functions, more specifically the Like function and its Inverse, in which CriptoDática is presented, an application Software developed by the authors, which seeks to assist in this association in a more practical and didactic way. Cryptography is currently an essential tool in the study of systems for building mathematical algorithms, having mathematical foundations, cryptography is based on principles and techniques when encoding and decoding messages that comprise a process of doing and undoing something, which is similar to the principle of the inverse function. Associating the teaching of functions with cryptography is a way to inform the student that everything he has studied so far, however basic, is applicable and useful. To produce the data of this survey, first there was the presentation of CriptoDática through a video tutorial along with the didactic proposal, later, the respondents were invited to answer a questionnaire through an online digital platform, Google forms, organized in thirteen questions and divided by two axes, the first axis is about the profile of teachers, the second axis is about the evaluation made of the CriptoDática application, through the experience and its pedagogical making for an analysis that converges to a necessary knowledge in relation to understanding this proposed tool. As a result, the CriptoDática tool proposal was acceptable, since the surveyed teachers considered it useful, since the use of CriptoDática, as well as, with the necessary adaptations and corrections in the future, could potentialize the association of the cryptology study with related functions and its inverse. And in the future, as extensions of this work, field research can be carried out in the classroom for students and teachers to evaluate the use of this learning object in teaching-learning activities, as well as new versions and other learning objects with new themes focused on cryptography to reach new audiences.